The Idioms of Mentawai Language Inmuntei Village - Mac Aditiawarman; Agustinus Sakukuret (Fakultas Sastra Universitas Ekasakti, 2018)
This thesis is about the idioms of Mentawai language in Muntei Village. Idiom is a word or phrase whose meaning is not obvious through knowledge of individual meanings of the constituent words but must be learnt as a whole. Idiom is something that has its own meaning and we cannot guess the meaning because it needs to be learnt to understand their meaning. The writer took the data from the elder in the community by doing an interview with the informant (a man) whose age is no more than 50 years old to make sure that the informant still remembers the right word of the idioms. Technique of collecting the data of this analysis is by doing the interview to the informant first, and then writes the data down in a table accordingly to their forms. In analyzing this data, the writer uses three theories from three experts. In order to analyze the forms of the idioms used by people in Muntei Village the writer uses the theory of idioms forms from Yayat Sudaryat. In order to analyze the syntactical functions of the idioms used by people in Muntei Village the writer uses the theory of syntactical functions of idioms from Jennifer Seidl and McMordie. Meanwhile for analyzing the meaning of the idioms, the writer uses the theory of idioms meaning from Aminuddin. The result shows that there are two forms of idioms that commonly found in Muntei Village, they are the full idioms (formed in sentence) and half idioms (formed in words or phrases). The result also shows that idioms have this syntactical function that make then can be placed as the subject, object, adjectives, and adverbs in the sentence. This research also shows that the meaning of the idioms that usually found in Muntei Village can only be understood by the people if they know who are the people involved in the conversation, what is the situation where the conversation occur, and what is the intention of using the idioms.